Factors Relating to The Incidence of Obesity in Women of Reproductive Age in The Working Area of The Community Health Center of Suak Ribee of Johan Pahlawan District of West Aceh Regency - Fitriani Fitriani; Teungku Nih Farisni; Yarmaliza Yarmaliza; Pipi Rahayu (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2019)
Obesity is a serious condition that can cause emotional and social problems. A person is considered overweight if his weight is 10% to 20% over his ideal body weight, while obesity occurs when a person has more than 20% over his ideal body weight. The working area of the Community Health Center (Puskesmas) of SuakRibeewas the area with the highest incidence of obesity in West Aceh with 89 cases. This study aims to find out the relationship between the incidenceof obesity and the factor of knowledge, diet, physical activity, family history of obesity, and occupation. This study is an analytical study with cross-sectional design. The sample in this study was all women of reproductive age in the working area ofPuskesmas of SuakRibee of Johan Pahlawan District of West Aceh Regency. The sample was taken using cluster sampling method, with a total of 98 people. The data analysis technique used was correlation test. Based on the results of the correlation test,it can be concluded that there was no relationship between the incidence of obesity and knowledge (p-value = 0.113> α = 0.05).However, there was a relationship between the incidence of obesity and diet (p-value = 0.030 <α = 0.05); physical activity (p-value = 0.021 <α = 0.05); family history of obesity (p-value = 0.034 <α = 0.05);and occupation (p-value = 0.000 <α = 0.05).